2019
DOI: 10.1016/j.addbeh.2018.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Youth say ads for flavored e-liquids are for them

Abstract: Introduction: E-cigarettes are the most popular tobacco product among adolescents and young adults ("AYA") and are available in many flavors. The e-cigarette industry argues that flavors are not meant to appeal to youth, yet no study has asked youth what age group they think ads for flavored e-liquids are targeting. We asked AYA which age group they thought ads for flavored eliquids targeted. Methods:In 2016 as part of a larger survey, a random sample of 255 youth from across California (62.4% female, mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…E-liquid marketing is focused on promoting flavors ( Laestadius, Wahl, Pokhrel, & Cho, 2019 ), and is known to enhance appeal, and intentions to use more than advertisements for non-flavored products ( Vasiljevic, Petrescu, & Marteau, 2016 ). Youth also believe that advertisements for flavored e-liquids target individuals similar to their own age ( McKelvey, Baiocchi, Ramamurthi, McLaughlin, & Halpern-Felsher, 2019 ). Findings from this study highlight that flavors are one of the key topics of discussions related to e-liquids on Twitter, which supports FDA's recent announcement about the need to regulate sale of flavored e-liquids, and e-cigarette products ( Food and Drug Administration, n.d. ).…”
Section: Discussionmentioning
confidence: 99%
“…E-liquid marketing is focused on promoting flavors ( Laestadius, Wahl, Pokhrel, & Cho, 2019 ), and is known to enhance appeal, and intentions to use more than advertisements for non-flavored products ( Vasiljevic, Petrescu, & Marteau, 2016 ). Youth also believe that advertisements for flavored e-liquids target individuals similar to their own age ( McKelvey, Baiocchi, Ramamurthi, McLaughlin, & Halpern-Felsher, 2019 ). Findings from this study highlight that flavors are one of the key topics of discussions related to e-liquids on Twitter, which supports FDA's recent announcement about the need to regulate sale of flavored e-liquids, and e-cigarette products ( Food and Drug Administration, n.d. ).…”
Section: Discussionmentioning
confidence: 99%
“…The claims by the e-cigarette industry sponsored research [55] that flavoured e-liquids are intended for adult smokers using e-cigarettes to quit smoking cigarettes and that flavours are not meant to appeal to youth is contradicted by their marketing strategies [56] . Young people (median age 18 years) believe advertisements for flavoured e-liquids target individuals about their age, not older adults [57] . Additionally advertisements for flavoured (vs. unflavoured) e-cigarettes elicit greater appeal and interest in buying and trying e-cigarettes [58] .…”
Section: Marketing Strategiesmentioning
confidence: 99%
“…Earlier studies on flavor additives revealed that adolescents perceived different flavors as healthier than unflavored products (World Health Organization, 2007). A more recent study found that many youths believe flavored e-liquid advertisements are meant for them and not the adults the companies claim to target (McKelvey, Baiocchi, Ramamurthi, McLaughlin, & Halpern-Felsher, 2019).…”
Section: Electronic Cigarette Terminologymentioning
confidence: 99%